JURISDICTIONAL AND ALTERNATIVE FORMS OF COPYRIGHT PROTECTION - KORCHOVYI, VALERII (Ehrlich's Journal, 2025)
The article examines the main forms of copyright protection, their normative nature, and practical effectiveness. Emphasis is placed on the transformation of copyright from a local regulatory mechanism of creative activity into a universal legal instrument that ensures the proper circulation of intellectual resources within the global information environment. It is argued that, in the context of rapid digital transformation, the optimal model for ensuring adequate protection and restoration of violated copyrights involves the interaction of both jurisdictional and non-jurisdictional forms. The advantages of the judicial mechanism for copyright protection are identified, particularly its role in establishing a consistent and stable practice in resolving intellectual property disputes. The study highlights the effectiveness of judicial protection in terms of the binding nature of decisions, procedural guarantees of fairness, and the establishment of enduring benchmarks in intellectual property law enforcement. At the same time, existing judicial and administrative procedures are characterized by significant time and financial costs due to bureaucratic constraints, and the potential deterioration of interpersonal and professional relations in the event of jurisdictional conflict resolution is noted. In this regard, the study pays special attention to alternative, non-jurisdictional forms of resolving copyright disputes. These forms are shown to be based on voluntariness, dispositiveness, equality, and consensus among the parties. The flexibility, dynamism, and confidentiality of such alternative procedures help preserve collaborative relationships and prevent further escalation of conflicts between creative actors. The research also focuses on the institutional capacity of the state to resolve intellectual property disputes at a highly professional and specialized level. In this context, the article underscores the urgent necessity of establishing a High Court on Intellectual Property as a mechanism to significantly improve the quality and effectiveness of law enforcement in this field. It is emphasized that the absence of such a specialized institution substantially complicates the proper protection and restoration of violated copyrights. It is argued that the exclusive combination of specialized jurisdiction and effective alternative procedures can ensure a flexible, efficient, and results-oriented system for copyright protection.